Designing a building for music and dance performing arts in Bogor - Agitia Gunawan; Yuke Ardhiati (Journal of Aesthetics, Creativity and Art Management, 2022)
This research aimed to design a building for music and dance performing arts in Bogor, West Java. In order to support the local government's work program, the building is designed so that art performers can create and express the results of these works and can be enjoyed by modern and contemporary art connoisseurs. Through such a building, West Java cultural arts can be preserved and inherited. The method used in the design refers to descriptive qualitative methods and uses literature studies and precedents, surveys and field observations. This is done in order to obtain complete data, then analyze every problem that exists. The resulting design concept is a building design with a cultural and modern atmosphere that is realized through a design theme, namely Semiotic and Taste Cultures with the intention of using a characteristic style that prioritizes simplicity of form, uses ornaments and follows the shape of the building's function.